Análisis de la gestión económica y financiera de la compañía Taxiflash S.A. 2015 – 2016. - Aguilar Aguilar, Jessica Maria (2017)
The research work is carried out in a local company, specifically in the company TAXIFLASH S.A .; Of the city of Machala, which is in charge of providing the service of transport of cargo and of people to the different places where it has its field of action and is authorized by the competent organisms; Is a group that has been offering its services for several years and has had a favorable reception by the population, which is why all the tools that contribute to establishing the most appropriate strategies that lead to expectations must be taken into account Of all its members, the main objective is to analyze the company in its economic and financial aspects to determine its current position with a view to an organizational horizon with favorable conditions and that are aligned to the interests of shareholders and other users of the services it provides The analysis is carried out through financial ratios or indicators, which allow to relate two or more amounts exposed in the legalized financial statements of the object of study, and that allow to visualize business scenarios in which the company has strengths and weaknesses that Should be corrected in the short term in order to Market with greater possibilities for sustainable growth; Among the main results obtained can be seen that the profitability is minimal compared to the assets invested, and reaches $ 0.01 per dollar of investment financed with own resources and others; Here it is very important to emphasize that the profitability is business since the charges for the services that are given fall directly on the owner of the means of transport and the cash inflows considered as income are determined by the monthly contributions of the members who alone Contribute to cover the company's administrative expenses; In this sense the analysis must be at the general level of the company under study and not individualized by each partner that if they obtain profitability in each service provided on a daily basis, at the end of the study the recommendations are issued, which are described in order to Contribute to business management and optimize resources more efficiently and achieve better economic horizons for the company. The study has its origin with the obtaining of the financial statements by the aforementioned company, for then and based on the techniques of the financial analysis, proceed to apply basic indexes that help to visualize its current positioning, for it It is necessary to use the inductive and inductive method, in order to synthesize the information of the research and also to summarize the theoretical information, in addition it is important to emphasize that it is a field study pro when it is carried out in a real scenario of a Local company, making necessary the qualitative factors to establish important situations in reference to the company and quantitative by the use of mathematical calculations proper to the economic and financial study carried out.